Primary Headache in Children and Adolescents: Update on Pharmacotherapy of Migraine and Tension-Type Headache - Bonfert, Michaela; Straube, Andreas; Schroeder, Andreas Sebastian; Reilich, Peter; Ebinger, Friedrich; Heinen, Florian (Neuropediatrics, 2013)
Primary headache disorders are frequently encountered in the pediatric population. The therapeutic approach consists of a multimodal program, including lifestyle modification, psychotherapeutic intervention, pharmacotherapy, and complementary measures. This systematic review focuses on the pharmacotherapy of pediatric migraine and tension-type headache (TTH). In addition to the general treatment principles, the results of 33 clinical reports published on the topic since 2008 are outlined in detail. Furthermore, a tabular summary of previously investigated agents not studied since 2008 is given, as is an overview of promising pharmacologic approaches so far only evaluated in adults. A variety of pharmacologic options is available, but high-quality evidence is limited to single agents. At this time, approval is restricted to four triptans and flupirtine for the symptomatic treatment of pediatric acute migraine and TTH, respectively. No agent has been approved for the prevention of pediatric primary headaches. This review does not grade the drugs hierarchically because the complex profiles of many agents differ only slightly or even overlap. However, a detailed expert opinion is provided. On the basis of the outlined facts, the team of physician, patient, and parents has to decide on the most appropriate regimen for the individual situation in the sense of personalized medicine.
Keywords: migraine; tension-type headache; acute headache treatment; preventive headache treatment; prophylactic headache treatment; pediatrics